2019
DOI: 10.1039/c9cc06858a
|View full text |Cite
|
Sign up to set email alerts
|

SO2 conversion to sulfones: development and mechanistic insights of a sulfonylative Hiyama cross-coupling

Abstract: A Pd-catalyzed Hiyama cross-coupling reaction using SO2 is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…13 C­{ 1 H} NMR (126 MHz, CDCl 3 ) δ 138.4, 133.9, 129.2, 128.7, 124.9, 124.8, 61.0 ppm. The spectroscopic data agree with the literature …”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…13 C­{ 1 H} NMR (126 MHz, CDCl 3 ) δ 138.4, 133.9, 129.2, 128.7, 124.9, 124.8, 61.0 ppm. The spectroscopic data agree with the literature …”
Section: Methodssupporting
confidence: 90%
“…The spectroscopic data agree with the literature. 61 Sulfonyldibenzene (3v). Compound 3v was synthesized following GP2 using diphenylsulfane (1v, 279 mg, 1.5 mmol) to give the product as a white solid.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It has been reported that Au-, , Cu-, and Pd-catalyzed , reactions of arylboronic acids and SO 2 surrogate lead to sulfinate salts. Recently, similar activation of organosilanes to generate sulfinates under metal-free conditions has been reported . We found that the three-component reaction between phenylboronic acids, K 2 S 2 O 5 , and CH 3 I gave PhSO 2 Me in 25% yield under heavy-metal-free conditions.…”
supporting
confidence: 70%
“…In presence of one equivalent of fluoride anions, a fluoride copper species is likely to be formed (A→C, ΔG = -3.2 kcal•mol −1 ) to then proceed to the transmetalation with the organosilane. 25 Although it has already been reported and experimentally evidenced that a stable FSO2 − anion is formed from DABSO and fluoride anions, 7,26 this adduct can also serve as a fluoride transfer agent to generate a copper(I) fluoride complex. As regards the transmetalation between the silane and the Cu-F species, computational results show a more favored transition state when the fluoride anion is in axial position on the silicon center (C→D, ΔG ≠ (TS2) = 19.2 kcal•mol −1 vs ΔG ≠ (TS2 ' ) = 24.9 kcal•mol −1 for the equatorial position, see ESI).…”
Section: Resultsmentioning
confidence: 98%
“…6 Recently, we described the first Pd-catalyzed sulfonylative Hiyama cross-coupling with sp 2 -hybridized electrophiles. 7 Surprisingly, only allylsilanes were found to react with sulfur dioxide, arylsilanes being inert under the reaction conditions. A careful mechanistic study unveiled that the organosilane was not involved in a transmetalation step, but instead reacting through a SE2' mechanism, restricting the scope to the formation of allyl aryl sulfones.…”
Section: Introductionmentioning
confidence: 99%